Machine Learning-based Virtual Screening and Its Applications to Alzheimer’s Drug Discovery: A Review - Carpenter, Kristy A. (Curr Pharm Des, 2018)
BACKGROUND: Virtual Screening (VS) has emerged as an important tool in the drug development process, as it conducts efficient in silico searches over millions of compounds, ultimately increas-ing yields of potential drug leads. As a subset of Artificial Intelligence (AI), Machine Learning (ML) is a powerful way of conducting VS for drug leads. ML for VS generally involves assembling a filtered train-ing set of compounds, comprised of known actives and inactives. After training the model, it is validated and, if sufficiently accurate, used on previously unseen databases to screen for novel compounds with desired drug target binding activity. OBJECTIVE: The study aims to review ML-based methods used for VS and applications to Alzheimer’s Disease (AD) drug discovery. METHODS: To update the current knowledge on ML for VS, we review thorough backgrounds, explana-tions, and VS applications of the following ML techniques: Naïve Bayes (NB), k-Nearest Neighbors (kNN), Support Vector Machines (SVM), Random Forests (RF), and Artificial Neural Networks (ANN). RESULTS: All techniques have found success in VS, but the future of VS is likely to lean more largely toward the use of neural networks – and more specifically, Convolutional Neural Networks (CNN), which are a subset of ANN that utilize convolution. We additionally conceptualize a work flow for con-ducting ML-based VS for potential therapeutics for AD, a complex neurodegenerative disease with no known cure and prevention. This both serves as an example of how to apply the concepts introduced earlier in the review and as a potential workflow for future implementation. CONCLUSION: Different ML techniques are powerful tools for VS, and they have advantages and disad-vantages albeit. ML-based VS can be applied to AD drug development.